2018
DOI: 10.1007/s13187-018-1417-6
|View full text |Cite
|
Sign up to set email alerts
|

Educating Hispanics About Clinical Trials and Biobanking

Abstract: Hispanics are under-represented in clinical research. To ensure that the Hispanic population benefits from advances in public health and medicine, including personalized medicine, there is a need to increase their participation in clinical trials and biobanking. There is a great need for improving awareness and addressing concerns individuals may have about participation. The purpose of this study was to adapt, implement, and evaluate educational materials about clinical trials and biobanking for Hispanic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…This study showed that the percentage of participants who had heard of the term biobanks in our population (3%) is significantly lower than those reported in other studies conducted in Finland, Jordan, Italy, and Germany, where the percentage of participants who had some knowledge of biobanks was between 9% and 36.5%. 17,24,[30][31][32][33][34][35][36][37] Knowledge of biobanks did not differ significantly between age groups or between men and women. Patients with a higher level of education were more likely to have already heard of biobanks.…”
Section: Discussionmentioning
confidence: 84%
“…This study showed that the percentage of participants who had heard of the term biobanks in our population (3%) is significantly lower than those reported in other studies conducted in Finland, Jordan, Italy, and Germany, where the percentage of participants who had some knowledge of biobanks was between 9% and 36.5%. 17,24,[30][31][32][33][34][35][36][37] Knowledge of biobanks did not differ significantly between age groups or between men and women. Patients with a higher level of education were more likely to have already heard of biobanks.…”
Section: Discussionmentioning
confidence: 84%
“…Hispanic or Latino adolescents are grossly underrepresented in clinical research trials, particularly those that involve biospecimen collection. [ 15 , 22 , 23 ] As a result, we consider it to be a great success that the proportion of Hispanic or Latino participants who enrolled in our study after referral compared to those who declined was so high. As described by Garcia et al (2017), a personal connection and direct contact with the research team are important to enroll Hispanic or Latino participants.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA recently published guidance on enrollment practices, eligibility criteria, and clinical trial design to enhance diversity [ 26 ]. Outreach by clinical trial sites to community physicians, leadership roles, committees committed to diversity, cultural training of physicians, community advisory boards and lay community representatives, culturally literate patient navigators, and culturally appropriate patient education [ 27 - 30 ] are all steps that have been shown to have a positive effect on minority clinical trial enrollment [ 18 - 21 ]. Recommendations to address minority distrust of HCPs include provider and support staff diversity, discussion of research transparency, and statement of overall clinical trial goals.…”
Section: Discussionmentioning
confidence: 99%